Examining dried noodle characteristics made from modified Xanthosoma sagittifolium flour and xanthan gum - Yurika Sugiharto; Ika Yohanna Pratiwi; Oki Krisbianto; Aham Bulan Maya Srihtam (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Gluten allergy has raised concerns due to its impact on health, especially as wheat noodles are widely consumed. The growing demand for gluten-free alternatives highlights the need for suitable substitutes. This study investigates the effects of fermentation modification on the amylose and protein content of tannia cocoyam flour and evaluates the impact of modified tannia flour and xanthan gum on the physicochemical and sensory properties of noodles. Fermentation of tannia cocoyam (Xanthosoma sagittifolium) corm flour using 9% Lactobacillus plantarum starter over 48 hours enhanced the characteristics of tannia cocoyam noodles. However, despite these improvements, the noodles remained brittle and lacked the desired chewiness compared to conventional noodles. The introduction of xanthan gum as a binding agent was used to improve noodle attributes. Various xanthan gum concentrations (0%, 1%, and 2%) were assessed for their impact on physicochemical parameters (color, optimal cooking time, rehydration capacity, cooking loss, and elongation) and sensory preferences. The findings revealed that modification of tannia cocoyam flour using the fermentation method influenced noodle color, while different xanthan gum concentrations had no discernible effect. Furthermore, modification of tannia cocoyam corm flour and the specific xanthan gum formulations influenced cooking loss, elongation, and the preferences of the panelists.